Nabokov's "Torpid Smoke" - Leona Toker (Studies in 20th & 21st Century Literature, 1988)
Nabokov's short stories are polished self-contained works of art. However, like his novels and poems, they can be profitably read in the light of their place in his general canon. This place is determined by the time when each story was written and by the way in which other works enrich and elucidate the significance of its images. The short fiction of Nabokov's Berlin period has been regarded largely as akin to studies that a painter makes in preparation for a big picture. In some cases, however, the stories seem to serve as safety valves for the urgent material that had to be kept out of the novels in order not to interfere with their design. A case in point is the 1935 story "Torpid Smoke," written at the juncture of Invitation to a Beheading and The Gift. The plight of the protagonist of "Torpid Smoke" is a hybrid of the tendencies manifest in Cincinnatus of Invitation and Fyodor Godunov Cherdyntsev of The Gift: however, unlike Fyodor, this young poet gets no encouragement in his wish to devote himself to literature; unlike Cincinnatus, he cannot reject his environment with a clear conscience. His father, the major obstacle to his literary pursuits, is essentially decent, well-meaning, and pathetically human—a far cry from the obnoxious "parodies" that surround Cincinnatus. The young poet is trapped between the exquisite happiness that accompanies poetic experience and the price that he cannot achieve artistic self-isolation. In a sense, the story dramatizes the conflict between morality and "aesthetic bliss." The imagery of the story ostensibly serves to increase the density of a plausible setting. Actually, the imagery is also functional; it forms a network of parallels and nuances that point both to the genuineness of the young man's talent and to the possible reason for the "puerile" quality of his "perishable" production, viz., to the presences of unprocessed issues whose pressure prevents him from successfully capturing his poetic experience in the flesh of language. The necessity of facing poignant complexities is a thematic undercurrent of the story. The story itself, moreover, seems to be Nabokov's way of confronting an issue of crucial relevance to Invitation and The Gift, viz., the morality of daily choices when the demands of personal relationships drain creative energies, yet cannot be rejected as cavalierly as in Invitation to a Beheading. In the design of The Gift there was no place for this theme; therefore Nabokov placed it in ' 'Torpid Smoke," his safety valve. He was then free to show the balance between communication and isolation maintained by the protagonist of The Gift.
Keywords: Nabokov; short stories; review; Torpid Smoke; Invitation to a Beheading; The Gift; Fyodor Godunov Cherdyntsev; poetry; morality; aestheticism; imagery; poetic expression; relationships; isolation; communication